Enhancing financial performance through absorptive capacity: Evidence from Croatian export companies in domestic and international markets - Ivana Martinčević (Business Systems Research (BSR), 2023)
Background: Export activities represent one of the prerequisites for the growth and development of economies. In combination with new digital technologies, they create a sustainable advantage and competitiveness in the market. Objectives: The focus of this research was to determine whether there is a significant difference and connection between the absorptive capacity of accepting new technologies and its influence on financial performance in the domestic and foreign markets. Methods /Approach: The relationship between the absorptive capacity of the application of new technologies and its influence on financial performance was investigated in a sample of Croatian companies. Structural equation modelling was used to investigate the relationship between absorptive capacity and financial performance. Results: The results of the research confirm a statistically significant relationship between the absorptive capacity of accepting new technologies and its influence on the financial performance of export companies. Conclusion: The analysis revealed that absorptive capacity significantly impacts the financial performance of Croatian export companies, with a stronger influence observed in foreign markets compared to domestic ones. These findings suggest that investing in the ability to absorb and apply new technologies is crucial for enhancing financial outcomes, particularly in the global marketplace.
Keywords: M1; O30; 330; absorptive capacity; new digital technologies; export; export companiesof the Republic of Croatia; sustainable development; Unternehmenserfolg; Technischer Fortschritt; Digitalisierung; Export; Kroatien